Integrated profiling uncovers prognostic, immunological, and pharmacogenomic features of ferroptosis in triple-negative breast cancer - Fang, Kun; Xu, Zhengjie; Jiang, Suxiao; Yan, Changsheng; Tang, Desheng; Huang, Yan (Frontiers in Immunology, 2022)
Objective Ferroptosis is an iron-dependent type of regulated cell death triggered by the toxic buildup of lipid peroxides on cell membranes. Nonetheless, the implication of ferroptosis in triple‐negative breast cancer (TNBC), which is the most aggressive subtype of breast carcinoma, remains unexplored. Methods Three TNBC cohorts—TCGA-TNBC, GSE58812, and METABRIC—were adopted. Consensus molecular subtyping on prognostic ferroptosis-related genes was implemented across TNBC. Ferroptosis classification-relevant genes were selected through weighted co-expression network analysis (WGCNA), and a ferroptosis-relevant scoring system was proposed through the LASSO approach. Prognostic and immunological traits, transcriptional and post-transcriptional modulation, therapeutic response, and prediction of potential small-molecule agents were conducted. Results Three disparate ferroptosis patterns were identified across TNBC, with prognostic and immunological traits in each pattern. The ferroptosis-relevant scoring system was proposed, with poorer overall survival in high-risk patients. This risk score was strongly linked to transcriptional and post-transcriptional mechanisms. The high-risk group had a higher response to anti-PD-1 blockade or sunitinib, and the low-risk group had higher sensitivity to cisplatin. High relationships of risk score with immunological features were observed across pan-cancer. Two Cancer Therapeutics Response Portal (CTRP)-derived agents (SNX-2112 and brefeldin A) and PRISM-derived agents (MEK162, PD-0325901, PD-318088, Ro-4987655, and SAR131675) were predicted, which were intended for high-risk patients. Conclusion Altogether, our findings unveil prognostic, immunological, and pharmacogenomic features of ferroptosis in TNBC, highlighting the potential clinical utility of ferroptosis in TNBC therapy.